Creating knowledge environment during lean product development process of jet engine - Araci, Zehra Canan; Al-Ashaab, Ahmed; Tariq, Muhammad Usman; Braasch, Jan H.; Emre Simsekler, M. C. (Science and Information Organisation, 2020)
Organizations invest intense resources in their product development processes. This paper aims to create a knowledge environment using trade-off curves during the early stages of the set-based concurrent engineering (SBCE) process of an aircraft jet engine for a reduced noise level at takeoff. Data is collected from a range of products in the same family as the jet engine. Knowledge-based trade-off curves are used as a methodology to create and visualize knowledge from the collected data. Findings showed that this method provides designers with enough confidence to identify a set of design solutions during the SBCE applications
Keywords: aircraft engine noise reduction; trade-off curves; set-based concurrent engineering; lean product development; new product development; knowledge management; Knowledge creation and visualization